Images Made by Contagion: On Dermatological Wax Moulages. (March 2022) - Fend, Mechthild
Moulages are contact media – images made by contagion in the most literal sense: their production relies on a process in which the object to be reproduced is touched by the reproducing material. In the case of dermatological moulages, the plaster touches the infected skin of the sick and, once dried, serves as the negative form for the waxen image of a disease. Focussing on the collection of the Hôpital Saint-Louis in Paris, the article situates the production of dermatological moulages within the visual culture of 19th-century medicine and raises the question how an ancient technique of image production could become such a prevalent tool for the documentation of skin diseases during a period usually associated with the rise of scientific medicine and a reconsideration of theories of contagion in medical aetiology.